Ethical considerations in the implementation of artificial intelligence systems for personnel selection and recruitment (Forseti. Law Review, 2025)
In this article, we will examine the impact of ethics on the use and development of artificial intelligence systems employed in personnel selection processes. To that end, we will analyze the concept of artificial intelligence, as well as that of ethics, and discuss recent laws that establish legal obligations for its use in hiring or selecting workers.
Keywords: Artificial Intelligence; Ethical Principles; Selection Process; Risk Prevention; Non-discrimination